Diameter-optimized PVA@PPy nanofibers: MXene interlayer space expansion without sacrificing electron transport. Issue 36 (22nd August 2022) - Li, Jinli; Cao, Zhiqian; Hu, Haibo; Ho, Derek
Abstract : PVA@PPy nanofibers are proposed as a novel spacer for MXene electrode interlayer space expansion in Zn-ion micro-supercapacitors. The PPy shell mitigates the well-known challenge of electron transport degradation due to the expansion. Abstract : Sluggish divalent and multi-valent ion diffusion in the MXene layers due to narrow physical space and strong coulomb interactions has been a formidable challenge in increasing the energy density of MXene-based micro-supercapacitor (MSC) electrodes. Although various types of spacer materials and structures have been reported, they are generally of a low charge storage capacity and electrical conductance, which significantly offset the benefit of introducing the spacer in the first place. This paper presents an electrospun PVA@PPy nanofiber suitable as a spacer for MXene electrodes, which significantly enhances energy density. The nanofiber combines the desirable mechanical strength of the PVA core and the high conductivity of the PPy shell. This simultaneously expands the interlayer space of a MXene host electrode for enhanced ion diffusion, while acting as electron conducting channels to mitigate the conductivity degradation due to the expansion. A zinc ion MSC (ZMSC) has been prototyped with the obtained MXene/PVA@PPy hybrid film electrodes, achieving an areal capacitance and energy density of 195 mF cm −2 and 38.4 μW h cm −2, respectively, at a current density of 0.2 mA cm −2, which corresponds to a specific energy density of 9.63 mW h g −1 . The dual functionality of the PVA@PPy nanofiber opens the door to a new breed of MXene interlayer spacers that are highly conductive, thus enabling MXene to exhibit both superior ion and electron transports for advanced electronic devices.